Creatine kinase kinetics in professional soccer players during a competitive season. - Daniel Barbosa Coelho; Rodrigo Figueiredo Morandi; Marco Aurélio Anunciação de Melo; Emerson Silami Garcia (Universidade Federal de Santa Catarina, 2011)
Serum creatine kinase (CK) concentration has been widely used as an indicator of skeletal muscle damage in sports. However, there are no longitunal studies on post-game CK kinetics in Soccer during a competitive season. The aim of this study was to evaluate serum CK kinetics in professional Soccer players at different post-game times during a competitive season without training interruption. Seventeen professional soccer players (age: 22.2±3.1 years, height: 179±6.0 cm, body fat percentage: 9.5±1.1, and 67.0±3.5 mL O2/kg/min) were evaluated over a period of 3 months of the national championship. Serum CK concentration was measured before the beginning of the season (baseline) and at four different times after a soccer game (post-1: 12-20 h, post-2: 36-48 h, post-3: 60-65 h, and post-4: 90-110 h). Plasma CK concentrations were higher at all times when compared to baseline (p<0.05). Post-2 CK concentration was lower than post-1 and higher than post-3 and -4 (p<0.05), with no significant differences between post-3 and post-4. In conclusion, serum CK kinetics was influenced by the training routine of the soccer players, with a peak between 12 and 20 h after the game, returning to normal within 60-65 h. This procedure can be used to monitor the recovery state of athletes and game and training intensities.